Formulasi Sediaan Salep Ekstrak Etanol Bawang Putih (Allium Sativum) dengan Variasi Basis - Nurhidayah Nurhidayah; Alifa Fitrah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Garlic is a medicinal plant that is widely used for health and is used by people for traditional medicine. Garlic contains various secondary metabolite compounds which have antifungal activity, including tannins, flavonoids, allicin. Flavonoids are the largest group of phenolic compounds. So it is possible that flavonoids also have an effective antifungal effect. This research aims to formulate an ethanol extract of garlic (Allium sativum) ointment with a variety of bases and to determine the physical quality of the ointment. The type of research is laboratory experimental. The method used is maceration of the extract using 1000 ml of 70% ethanol, the design of the ointment formulation is to use three base variations FI (Hydrocarbon Base), FII (Absorption Base), FIII (Water Soluble Base). The results of the research conducted show that ethanol extract of garlic (Allium sativum) can be formulated into an ointment and has stable physical quality. The conclusion from this research is that ethanol extract of garlic (Allium sativum) can be formulated into an ointment and has stable physical quality.